Analisis Pengendalian Kualitas Produk dengan Menggunakan Metode Statistical Quality Control (Sqc) untuk Mengurangi Produk Cacat - Anisya Islamiyani; Tasya Aspiranti; Cici Cyntiawati (Bandung Conference Series: Business and Management, 2022)
Abstract. Convection Berkah is a company that produces children's clothing. One of the main challenges that this company often faces is that the production process has been carried out properly, but in reality the problem of defective products is still quite high and even tends to increase. The purpose of this study was to obtain a study on the implementation of quality control of children's clothing products carried out by Berkah Convection in an effort to minimize defective products. The method for data processing and analysis was carried out using the Statistical Quality Control method. The results showed that the implementation of quality control of children's clothing products that had been carried out by Convection Berkah in an effort to minimize defective products was carried out on raw materials, production processes, and finished products. The application of the Statistical Quality Control method is appropriate for controlling the quality of children's clothing products. The most common quality characteristic or type of defect that occurs in the production process of making children's clothing is untidy stitches. Based on the cause-and-effect diagram, there are four factors that cause the problem of the emergence of this type of defect, namely humans, machines, raw materials, work methods and the environment. Abstrak. Konveksi Berkah merupakan perusahaan yang memproduksi pakaian anak. Salah satu tantangan utama yang sering dihadapi perusahaan ini adalah proses produksi telah dilaksanakan dengan baik, namun realitasnya masalah produk cacat masih cukup tinggi bahkan cenderung meningkat. Tujuan dari penelitian ini adalah untuk memperoleh kajian tentang pelaksanaan pengendalian kualitas produk pakaian anak yang dilakukan oleh Konveksi Berkah dalam upaya meminimumkan produk cacat. Metode untuk pengolahan dan analisis data dilakukan dengan menggunakan metode Statistical Quality Control. Hasil penelitian menunjukkan bahwa pelaksanaan pengendalian kualitas produk pakaian anak yang telah dilakukan oleh Konveksi Berkah dalam upaya meminimumkan produk cacat dilakukan atas bahan baku, proses produksi, dan produk jadi. Penerapan metode Statistical Quality Control tepat digunakan untuk pengendalian kualitas produk pakaian anak. Karakteristik kualitas atau jenis cacat paling banyak terjadi pada proses produksi pembuatan pakaian anak adalah jahitan tidak rapi. Berdasarkan diagram sebab-akibat terdapat empat faktor penyebab permasalahan munculnya jenis cacat yaitu manusia, mesin, bahan baku, metode kerja dan lingkungan.